Public School Taxes and the Remaking of Suburban Space and History: Etobicoke, 1945–1954 - Ellis, Jason (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2019)
This article examines public school taxes, housing, and changing suburban space in Etobicoke Township (suburban Toronto) between 1945 and 1954. Bridging educational and urban and suburban history, and incorporating recent insights from tax history, it examines the role that school taxes played in transforming Etobicoke from a rural and income-mixed pre-war suburb into a more middle-class, homogenous post-war one. School trustees taxed the new, middle-class housing being constructed in the suburb to underwrite educational expenditures that expanded and modernized the Etobicoke public school system. At the same time, tax and other public policy excluded lower-value rental housing and small dwellings, and also excluded their residents, who did not contribute enough in property taxes to support the emerging suburban school system. School taxes marked inclusion and exclusion in changing Etobicoke. As suburban space changed, established working-class residents and farmers tried to defend their interests as school taxpayers. Farmers could not defend their interests in the same way, and many sold their properties to sub-dividers for housing, erasing farms and one-room schools from the suburban landscape. The history of suburbanization and the history of educational expansion and modernization were causatively dependent on one another. Historians of education and urban and suburban historians benefit from drawing on each other’s aligned historiographies, and from looking at taxes.